Effects of nail softness and stiffness with distance running shoes on ground reaction forces and vertical loading rates in male elite long-distance runners with pronated feet - Jafarnezhadgero, A. A.; Fakhri, E.; Granacher, U. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background To improve propulsion during running, athletes often wear spike shoes designed for training and/or competition. Running with spike shoes may cause pain and/or injuries. To address this problem, a modified spike shoe was tested. This study aimed to evaluate the effects of running with dual-versus single-stiffness spike running shoes on running mechanics in long-distance runners with pronated feet.